The Syntactic and Semantic Changes Associated with the Use of Modulation in English-Arabic Translation - Alwazna, Rafat (International Journal of Linguistics and Translation Studies, 2022)
Modulation is a procedure categorized under oblique translation method. The present paper addresses the semantic and syntactic changes associated with the use of modulation in English-Arabic translation. It seeks to present all the ten types of modulation, devoting an example for each type, to elucidate the semantic and syntactic changes made on the modulated Arabic target text as compared to the literal Arabic translation. Based on the data used, the paper argues that both obligatory and optional modulations are employed in English-Arabic translation. Semantically, obligatory modulations are adopted when the literal meaning is not intended, when English and Arabic use different figurative words to express the same notion or when they use different symbols to indicate the same concept. Optional modulations are employed to serve stylistic purposes, keep the words collocate with one another, produce naturalness, adopt preferred structures and specify space or time. Syntactically, the English source text and the modulated Arabic target text are similar whenever Arabic starts with a noun and are different otherwise. Finally, the modulated Arabic target text and the literal Arabic translation are identical whenever they both either start with a noun or a verb and are different when they possess different structures.